2023
DOI: 10.1002/pat.6122
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐friendly three‐dimensional hydrogels for sustainable agricultural applications: Current and future scenarios

Abstract: Modern world is searching for water efficient agriculture techniques as irrigation is becoming scarce. Limited water resources and more food demand are the two key challenges in agriculture. Hydrogels which can respond intelligently by pH, temperature, light, ionic strength, osmotic pressure, magnetic or electric field changes are termed as intelligent or smart hydrogels which are analogous to conventional hydrogels in preparatory methods and features. Lag phase, constant release and decay phase are three step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 119 publications
(192 reference statements)
1
4
0
Order By: Relevance
“…Sasmal and Patra (2020) [ 41 ] reported that the quantity of water retained in the soil increased significantly with CMH inclusion, resulting in controlled water release under dry conditions. This observation aligns with Azeem et al (2023) [ 42 ], who attributed plant growth to CMH's effective water retention and gradual release capabilities, ensuring a consistent and controlled moisture supply to plant roots. Similarly, Prisa and Guerrini (2022) [ 43 ] reported increased Solanum lycopersicum plant height, vegetative growth, seed germination, and microbial colonization of the substrate with two or three hydrogel (Hydro Start) capsules under drip irrigation.…”
Section: Resultssupporting
confidence: 90%
“…Sasmal and Patra (2020) [ 41 ] reported that the quantity of water retained in the soil increased significantly with CMH inclusion, resulting in controlled water release under dry conditions. This observation aligns with Azeem et al (2023) [ 42 ], who attributed plant growth to CMH's effective water retention and gradual release capabilities, ensuring a consistent and controlled moisture supply to plant roots. Similarly, Prisa and Guerrini (2022) [ 43 ] reported increased Solanum lycopersicum plant height, vegetative growth, seed germination, and microbial colonization of the substrate with two or three hydrogel (Hydro Start) capsules under drip irrigation.…”
Section: Resultssupporting
confidence: 90%
“…Smart hydrogel composites, with their ability to swell upon water immersion while maintaining structural integrity, hold significant promise as smart materials. Their applications span diverse fields, from biomedicine including drug delivery devices [ 89 ], artificial organs, and tissue engineering [ 19 , 90 ], to agriculture [ 91 , 92 ]. In 4D printing, these hydrogel composites present an innovative method for various applications such as custom-designed sensors and robotics [ 19 , 85 , 86 ].…”
Section: Smart Polymer Materials For 4d Printingmentioning
confidence: 99%
“…Smart hydrogels for agricultural applications were recently developed and investigated [14,15]. Obtained results and characteristics were described in several reviews [16][17][18][19]. Zhang et al [14] developed new multifunctional smart soils with double-layer structures consisting of zwitterionic, thermo-responsive poly(NIPAM-co-VPES), and poly(NIPAM-co-SBAA) aerogels doped in the upper layer and the bottom bed of the soils, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Another review encompassed the latest developments in the field of smart hydrogel synthesis based on their unique features and different aspects of their responsive behaviors was published by Sikdar et al [17]. Azeem et al [18] published the review that spotlighted application prospects of three-dimensional hydrogel in agriculture. Hydrogel functioning, significance, advantages, mechanism of fertilizer release, and agriculture-specific applications were comprehensively described.…”
Section: Introductionmentioning
confidence: 99%